FAKTOR-FAKTOR YANG MEMPENGARUHI NAIK – TURUNNYA HARGA CABAI MERAH MENURUT PENDAPAT PETANI DI KABUPATEN SITUBONDO (Studi Kasus di Desa Arjasa, Kec. Arjasa, Kab. Situbondo) - Yoki Hendra Sugiarto; Yohanes Nangameka (AGRIBIOS, 2013)
The purpose of research is describing the development trend of chili price in Situbondo and identifying factors that affect the price fluctuation of chili in Situbondo. Method of determining the research area is purposive method that is the research area is determined intentionally by consideration of the scale of chili production rate, sampling method was also conducted with purposive method with considering that the sample is the Situbondo farmers who commercialize red chili plant in 2012 or in the previous years, and the number of sample is 40 farmers. The data collected consist of primary data and secondary data obtained through interview and data from the relevant institution. Data analysis method that is used is multiple linear regression analysis method with dummy equation model to see how the development trend of the chili price in the research area, as well as using multiple linear regression factor analysis to identify factors that affect the price fluctuation of red chili in the research area. The research result shows the development of the chili price in Situbondo is fluctuative and tends to constant. The positive factors that influence price fluctuation of red chilies in Situbondo are seed price, chemical fertilizer price, pesticide price, mulch price, polybag price, weather/climate, celebration of religious feast days, and marketing cost.